Enredos= Lingkaran. - Arena Wati. (Institut Terjemahan & Buku Malaysia, 2010)
The novella Lingkaran (Endredos) originally titled Tumbangnya Pokok Tak Berlangit,The Fallen Tree Can No Longer Rise), was awarded the Dewan Bahasa dan Pustaka (Malay Language Center and National Library) prize in 1962, in the novel competition. Lingkaran is one of the most renowned works of the author Arena Wati. The theme of the novella traces the fates and dilemmas facing the Malays during the early days of the country's independence and development. In the story, the author entertainingly presents the idiosyncrasies of the different ethnic groups, their characteristics, and new lifestyles. Arena Wati recounts the adventures of the characters while the expectations, fears, and doubts of each one of them are threaded together in search of their destinies in independent Malaysia and what it means for this multiracial society, to be part of the new national reality, full of ups and downs,